Laboratory-Based Assessment of Cypermethrin Neurotoxic Insecticide Efficacy for Aedes aegypti Vector Control Dir Lower (The Research of Medical Science Review, 2024)
Laboratory-Based Assessment of Cypermethrin Neurotoxic Insecticide Efficacy for Aedes aegypti Vector Control Dir Lower. The mortality rates were assessed at various time intervals after treatment (24h, 48h, 72h, 96h, and 120h) and compared with control groups. Results showed that after 24 hours, Cypermethrin induced a 45% mortality rate, which increased significantly to 81.81% at 48 hours. At 72 hours, complete mortality (100%) was observed. However, by 96 and 120 hours, mortality rates dropped to 0%, suggesting a limited residual effect. The control group demonstrated minimal mortality throughout the study, highlighting the effectiveness of Cypermethrin as a rapid insecticide for controlling Aedes aegypti in outbreak situations.